EFFECT OF INHIBITED MICROBIAL ACTIVITY ON PORCELLIO LAEVIS (ISOPODA : CRUSTACEA) MEDIATED LEAF LITTER DECOMPOSITION - JOY, V.C.; JOY, S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1997)
The role of soil arthropod decomposer fauna in enhancing chemical degradation of organic matter has been highlighted in the present laboratory study by comparing the effect of feeding by Porcellio laevis (terrestrial isopods) under partial inhibition of microbial activity (using amplicillin as bactericide) on the leaf litter of kadam' (Anthocephalus chinensis) and cassia (Cassia siamea) trees. The feeding effects were compared with respect to total soluble carbohydrates, total proteins and CO2, evolution, Drastic decline in the amount of both macronutrients could be observed within 15 days in kadam litter. Ampicillin did not affect degradation of proteins. Feeding by P. laevis significantly decreased the level of carbohydrates but could not deplete proteins. In both litter types the rate of CO2: production was higher in amplicillin treated sets which could also enhance the rate of respiration by P. laevis more evidently in kadam litter. P. laevis while utilizing the carbohydrate resources could obtain more energy from fast decomposing leaf litter.